Medical language for modern health care - Allan, David 1942- (Robert Stephen); Lockyer, Karen D. 1955- 1963- 1945- Pamela A. Erminio Peter (New York, NY McGraw-Hill, 2011)
Anatomy of word building : the language of health care -- The body as a whole : the language of anatomy -- Integumentary system : the language of dermatology -- Special senses of the eye and ear : the language of ophthalmology and otology -- Musculoskeletal system : the language of orthopedics -- Digestive system : the language of gastroenterology -- Blood : the language of hematology -- Cardiovascular system : the language of cardiology -- Respiratory system : the language of pulmonology -- Nervous system : the language of neurology -- Urinary system : the language of urology -- Male reproductive system : the language of reproduction -- Female reproductive system : the languages of gynecology and obstetrics -- Endocrine system : the language of endocrinology -- Lymphatic and immune systems : the language of immunology -- Life span : the languages of pediatrics and gerontology -- Nutrition : the language of nutrition -- Rehabilitation medicine : the language of rehabilitation -- Mental health : the languages of psychology and psychiatry -- Infection : the language of infectious diseases -- Genetics : the language of DNA -- Cancer : the language of oncology -- Complementary and alternative medicine : the language of CAM.
Includes index.
Keywords: Medicine -- Programmed instruction -- Terminology; Medicine; Terminology as Topic; Y học; Ngôn ngữ y học; Chăm sóc sức khỏe